Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Microbiome baseline for an Arctic sentinel: spatial patterning of nasal and anal microbiomes in ringed seals - Carlos A. Domínguez-Sánchez; Olwyn C. Friesen; Brent G. Young; Tera L. Edkins; Ellen V. Lea; Magali Houde; Stephen D. Petersen; David J. Yurkowski; Holly E. L. Gamblin; Steve H. Ferguson (Frontiers in Marine Science, 2026)
Introduction Ringed seals ( Pusa hispida ) are sentinel species of Arctic change, yet baseline microbiome data across their circumpolar range remain limited. Methods We profiled nasal and anal microbiomes from 90 free-ranging ringed seals across eight Arctic and sub-Arctic locations in Canada using 16S rRNA gene amplicon sequencing. Results Body site was the primary determinant of microbiome structure, with nasal and anal assemblages forming distinct communities that could be classified with 94.8% accuracy, consistent with strong niche partitioning. Nasal microbiomes exhibited a conserved core dominated by the genera Corynebacterium, Psychrobacter , and Suttonella across all sampling locations, supporting a stable respiratory baseline consistent with host-mediated filtering. In contrast, anal microbiomes showed higher richness, greater inter-individual variability, and a latitudinal gradient in diversity: Shannon index, Pielou’s evenness, and Simpson index all declined with increasing latitude (all p < 0.05), suggesting that ecological constraints at higher latitudes promote dominance by a narrower set of taxa without reducing overall richness. Despite overall compositional differences among locations, geographic distance was a poor predictor of microbiome dissimilarity in both body sites. Instead, continuous spatial gradients of latitude and longitude were associated with microbiome composition in both body sites: in nasal microbiomes, genus Corynebacterium increased while Ornithobacterium and Suttonella decreased at higher latitudes, whereas in anal microbiomes, Psychrobacter and Peptoclostridium increased northward while Fusobacterium and Bacteroides declined, patterns not previously reported in Arctic pinnipeds. Conclusion Together, these findings establish the first integrated nasal and anal microbiome baseline for ringed seals, demonstrate that the two body sites provide complementary ecological signals, and establish a reference framework for future microbiome-based health monitoring in a rapidly changing Arctic.

Top‐Down and Bottom‐Up Processes Jointly Explain Mesopredator Movement and Foraging Ecology - Katie R. N. Florko; Tyler R. Ross; Steven H. Ferguson; Joseph M. Northrup; Martyn E. Obbard; Gregory W. Thiemann; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2026)
Prey availability and predation risk drive animal distribution, movement, and foraging ecology, yet studies rarely analyse multiple predator–prey levels together. Understanding how predators optimise risk–reward tradeoffs is important for species conservation and management, especially in systems facing extreme ecosystem change. We examined how top‐down (modelled polar bear habitat selection) and bottom‐up (modelled fish diversity) processes influence the habitat selection, movement, and foraging behaviour of 26 ringed seals (greater than 70,000 dives and 10,000 locations over 877 seal days). Our results suggest that polar bears spatially restrict seal movements and reduce the time seals spend foraging, potentially decreasing foraging success. Seals were more likely to be present and dive longer in high‐predation risk areas when prey diversity was high. Further, seal habitat selection models excluding polar bears overestimated core space use. These findings illustrate the dynamic tradeoffs that mesopredators make when balancing predation risk and resource acquisition.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

You are the colour of what you eat: higher invertebrate consumption correlates with redder muscle pigmentation in anadromous Arctic char (Salvelinus alpinus) along western Hudson Bay, Nunavut, Canada - Connor W. Faulkner; Sonny J. Ittinuar; Clayton U. Tartak; Vincent L’Herault; Les N. Harris; Gail K. Davoren; David J. Yurkowski (Marine Biology, 2025)
Salmonid fishes exhibit marked intra-specific variation in muscle pigmentation, primarily due to individual differences in the accumulation and assimilation of dietary carotenoids. Carotenoids are synthesized by primary producers and microorganisms, and present in the tissues of crustaceans that can serve as important prey for salmonids. Despite anadromous Arctic char ( Salvelinus alpinus ) being a key subsistence and economic resource across Inuit Nunangat, their muscle pigmentation in relation to diet and environmental variability (e.g., sea ice dynamics) has not been investigated. Using carotenoid spectrophotometry analysis and a muscle colour scale, we examined the influence of Arctic char diet, inferred from stomach contents, stable isotopes (δ 15 N), and highly branched isoprenoids on their muscle pigmentation, as well as muscle pigmentation of their prey near the communities of Rankin Inlet and Naujaat, Nunavut in two years (2021, 2022) with contrasting sea ice cover. Among prey types, invertebrates had higher carotenoid concentrations than fishes. Arctic char in Naujaat contained higher muscle carotenoid concentrations and redder muscle than in Rankin Inlet in 2021, associated with a higher invertebrate-based diet and more prevalent sea ice cover. In 2022, muscle carotenoid concentrations of Naujaat and Rankin Inlet Arctic char were similar, associated with a largely fish-based diet and similar sea ice cover, although muscle still remained redder in Naujaat Arctic char. Inter-annual variation in carotenoid concentration and muscle pigmentation associated with diet variability observed in this species may affect local resource users over the long-term due to unpredictable climate-driven environmental changes, resulting in socioeconomic impacts across the Arctic.

Spatiotemporal variation in foraging ecology and mercury concentrations in ringed seals and bearded seals across a latitudinal gradient in the eastern Canadian Arctic - R. Janelle Laing; Jean-Pierre W. Desforges; Kallie S. Strong; Debbie Armstrong; Feiyue Wang; Steven H. Ferguson; David J. Yurkowski (Environmental Research, 2025)

Migratory Arctic char ( Salvelinus alpinus ) as a prey pulse for Arctic marine predators - Matthew J. H. Gilbert; Les N. Harris; Alexander L. Vail; Kristin L. Laidre; Mark L. Mallory; David J. Yurkowski (Ecology, 2025)

Biologging reveals rapid movements of harbour seals between freshwater and marine habitats in the subarctic - Katie R.N. Florko; David J. Yurkowski; C-Jae C. Breiter; Steven H. Ferguson; Holly E.L. Gamblin; Adam Grottoli; Andrea Nace; Courtney R. Shuert; Stephen D. Petersen (Frontiers in Marine Science, 2024)
Biologging tools can provide invaluable information on the movement and behaviour of animals, facilitating the elucidation of ecological dynamics, especially for wide-ranging species, and supporting conservation and management efforts. Harbour seals ( Phoca vitulina ) exhibit extensive habitat plasticity in their vast range across the northern hemisphere, with likely recent increases in abundance at northern latitudes, yet details of their movement behaviour in subarctic areas remain largely unknown. We used satellite-telemetry data, including nearly 5,000 locations and over 12,000 dives, obtained from six harbour seals tagged in western Hudson Bay from 2021 to 2023, to address the knowledge gap on their movement behaviour between marine and freshwater habitats in subarctic regions. We document the behavioural patterns, transit speeds, and diverse aquatic system usage, including detailed records of a harbour seal track traversing over 170 km upriver on three separate trips along the Seal River, Canada. Notably, we observed a rapid downstream transit from the Seal River to Hudson Bay, covering 214 km within a single day. Additionally, we highlight the prevalence of short dive durations in the Seal and Churchill Rivers, in contrast to longer dive durations in Hudson Bay. These insights complement existing evidence of harbour seal occurrences and river use at northern latitudes, as well as enhance our understanding of harbour seal movement ecology within Hudson Bay which can be used to better inform conservation and management strategies between connected freshwater and marine environments in the Arctic.

Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.

A review of aerial survey density estimates of bearded seals (Erignathus barbatus) in the Canadian Arctic highlights important knowledge gaps and research needs - Matthew Fuirst; Steven H. Ferguson; Jeff W. Higdon; Brent G. Young; Ellen V. Lea; William R. Koski; David J. Yurkowski (Polar Biology, 2023)
There has been significant sea ice loss in the Arctic as a result of climate change, with measurable impacts on available habitat for ice-obligate marine mammals. Bearded seals ( Erignathus barbatus ) have a circumpolar distribution and primarily inhabit coastal areas of shallower depths with seasonal pack ice cover. However, there is limited information and no formal estimates on population abundance and densities of bearded seals within Canada. Here, we review historic field reports and publications from aerial surveys conducted from 1974 to 2022 to compile the density and abundance estimates of bearded seals across Canadian waters. Aerial surveys for marine mammals have been flown in several areas across the Canadian Arctic, including the Beaufort Sea (1974–2006), Canadian High Arctic (1979–2022), Baffin Bay-Davis Strait (1979–2014), and the Hudson Complex (1994–2017). After reviewing all published data sources, we report that the density of bearded seals in Canada were highest (and highly variable) in the Beaufort Sea (0.01–8.68 seals*km −2 ), then in Baffin Bay-Davis Strait (0.004–8.3 seals*km −2 ), and lowest and less variable inter-annually in the Hudson Complex (0.02 to 0.12 seals*km −2 ) at the time of these surveys. We also determined that bearded seals are more often found in areas of patchy ice cover (50–75%) with shallow water depths ≤ 500 m. Further, this review identifies regions within the Canadian Arctic and sub-Arctic that require updated aerial survey information. Quantifying the abundance and density estimates of bearded seals in Canada is essential for monitoring population status over time to better understand how this species is responding to environmental variation from anthropogenic activity and climate change.

Habitat coupling dynamics of mobile consumers along a freshwater and marine resource gradient in a sub-Arctic estuarine system - Jillian R. St George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuarine, Coastal and Shelf Science, 2023)

Mercury accumulation, biomagnification, and relationships to δ13C, δ15N and δ34S of fishes and marine mammals in a coastal Arctic marine food web - David J. Yurkowski; Elena McCulloch; Wesley R. Ogloff; Kelsey F. Johnson; Rémi Amiraux; Niladri Basu; Kyle H. Elliott; Aaron T. Fisk; Steven H. Ferguson; Les N. Harris; Kevin J. Hedges; Kevin Jacobs; et al. (Marine Pollution Bulletin, 2023)

Multi-dietary tracer approach reveals little overlap in foraging ecology between seasonally sympatric ringed and harp seals in the high Arctic - Jean-Pierre Desforges; Doreen Kohlbach; Cody G. Carlyle; Christine Michel; Lisa L. Loseto; Bruno Rosenberg; David J. Yurkowski; Steven H. Ferguson (Frontiers in Marine Science, 2022)
The rapid rate of climate change in the Arctic is causing broad-scale changes to the physical environment and biological communities. Characterizing the foraging ecology and habitat use of Arctic marine top predators of high ecological and cultural significance is essential to our understanding of their vulnerability to ecosystem change, especially when there is potential for dietary resource competition in spatially co-occurring species. We therefore undertook this study to explore dietary resource competition between seasonally sympatric ringed seals ( Pusa hispida ) and harp seals ( Pagophilus groenlandicus ) in Mittimatalik (previously known as Pond Inlet), Nunavut, Canadian Arctic. We used bulk stable isotopes (δ 13 C and δ 15 N), fatty acid-specific carbon isotopes (δ 13 C), fatty acid profiles, and diatom lipid biomarkers in a multi-tracer framework to track carbon and trophic pathways in liver and muscle of both seal species. Altogether, the dietary tracers showed little overlap in the diet between ringed seals and harp seals when they co-occurred in the open-water season in northwest Baffin Bay. Though a high dependence on sea ice-derived carbon sources for both species was found, dietary tracers suggested that ringed seals relied to a far greater extent on sympagic carbon sources (~80% vs. 50% for harp seals) and a greater extent of benthic/coastal prey species compared to the more pelagic feeding harp seals. Ringed seal samples were available year-round, and analyses revealed a clear seasonal pattern of foraging on sympagic and benthic prey during ice-covered months of the year and shifting to greater reliance on pelagic prey during the summer open-water season. Overall, ringed seals may be more vulnerable to changes in sea-ice dynamics in the rapidly changing Arctic than harp seals, though it remains difficult to predict future dietary plasticity and competition between co-occurring top predators in an increasingly ice-free Arctic with a changing prey community.

Predicting how climate change threatens the prey base of Arctic marine predators - Katie R. N. Florko; Travis C. Tai; William W. L. Cheung; Steven H. Ferguson; U. Rashid Sumaila; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2021)
Arctic sea ice loss has direct consequences for predators. Climate‐driven distribution shifts of native and invasive prey species may exacerbate these consequences. We assessed potential changes by modelling the prey base of a widely distributed Arctic predator (ringed seal; Pusa hispida ) in a sentinel area for change (Hudson Bay) under high‐ and low‐greenhouse gas emission scenarios from 1950 to 2100. All changes were relatively negligible under the low‐emission scenario, but under the high‐emission scenario, we projected a 50% decline in the abundance of the well‐distributed, ice‐adapted and energy‐rich Arctic cod ( Boreogadus saida ) and an increase in the abundance of smaller temperate‐associated fish in southern and coastal areas. Furthermore, our model predicted that all fish species declined in mean body size, but a 29% increase in total prey biomass. Declines in energy‐rich prey and restrictions in their spatial range are likely to have cascading effects on Arctic predators.

Biomarkers in Ringed Seals Reveal Recent Onset of Borealization in the High- Compared to the Mid-Latitude Canadian Arctic - Camille de la Vega; Claire Mahaffey; David J. Yurkowski; Louisa Norman; Elysia Simpson; Sophie Smout; Steven H. Ferguson; Rachel M. Jeffreys (Frontiers in Marine Science, 2021)
Warming of the Arctic has resulted in environmental and ecological changes, termed borealization, leading to the northward shift of temperate species. Borealization has occurred across all trophic levels, altering the structure of the food web. The onset and rate of borealization likely varies with latitude, depending on local warming and advection of warmer water into the Arctic. In order to assess latitudinal trends in food web structure in the Arctic, we analyzed stable nitrogen isotopes of specific amino acids alongside bulk stable carbon isotopes in ringed seal muscle tissue from the Canadian Arctic Archipelago (high-Arctic) and Southern Baffin Bay (mid-Arctic) from 1990 to 2016. Our results indicate a shift in food web structure in the high-Arctic that has occurred more recently when compared with the mid-Arctic. Specifically, over the past 25 years, the trophic position of ringed seals from the mid-Arctic was largely constant, whereas the trophic position of ringed seals decreased in the high-Arctic, reaching similar values observed in the mid-Arctic in 2015–2016. This suggests a potential shortening of the food chain length in the high-Arctic, possibly driven by changes in zooplankton communities feeding complexity in association with sea ice decline. This study identifies a temporal offset in the timing of borealization in the Canadian Arctic, resulting in different response of food webs to ecological changes, depending on latitude.

Determining the appropriate pretreatment procedures and the utility of liver tissue for bulk stable isotope ( δ 13 C and δ 15 N ) studies in sharks - K. Blue Pahl; David J. Yurkowski; Sabine P. Wintner; Geremy Cliff; Matthew L. Dicken; Nigel E. Hussey (Journal of Fish Biology, 2021)
Stable‐isotope analysis (SIA) provides a valuable tool to address complex questions pertaining to elasmobranch ecology. Liver, a metabolically active, high turnover tissue (~166 days for 95% turnover), has the potential to reveal novel insights into recent feeding/movement behaviours of this diverse group. To date, limited work has used this tissue, but ecological application of SIA in liver requires consideration of tissue preparation techniques given the potential for high concentrations of urea and lipid that could bias δ 13 C and δ 15 N values ( i.e ., result in artificially lower δ 13 C and δ 15 N values). Here we investigated the effectiveness of (a) deionized water washing (WW) for urea removal from liver tissue and (b) chloroform‐methanol for extraction of lipids from this lipid rich tissue. We then (a) established C:N thresholds for deriving ecologically relevant liver isotopic values given complications of removing all lipid and (b) undertook a preliminary comparison of δ 13 C values between tissue pairs (muscle and liver) to test if observed isotopic differences correlated with known movement behaviour. Tests were conducted on four large shark species: the dusky (DUS, Carcharhinus obscurus ), sand tiger (RAG, Carcharias taurus ), scalloped hammerhead (SCA, Sphyrna lewini ) and white shark (GRE, Carcharodon carcharias ). There was no significant difference in δ 15 N values between lipid‐extracted (LE) liver and lipid‐extracted/water washed (WW) treatments, however, WW resulted in significant increases in %N, δ 13 C and %C. Following lipid extraction (repeated three times), some samples were still biased by lipids. Our species‐specific “C:N thresholds” provide a method to derive ecologically viable isotope data given the complexities of this lipid rich tissue (C:N thresholds of 4.0, 3.6, 4.7 and 3.9 for DUS, RAG, SCA and GRE liver LEWW tissue, respectively). The preliminary comparison of C:N threshold corrected liver and muscle δ 13 C values corresponded with movement/habitat behaviours for each shark; minor differences in δ 13 C values were observed for known regional movements of DUS and RAG (δ 13 C Diffs = 0.24 ± 0.99‰ and 0.57 ± 0.38‰, respectively), while SCA and GRE showed greater differences (1.24 ± 0.63‰ and 1.08 ± 0.71‰, respectively) correlated to large‐scale movements between temperate/tropical and pelagic/coastal environments. These data provide an approach for the successful application of liver δ 13 C and δ 15 N values to examine elasmobranch ecology.

Diet and isotopic niche overlap elucidate competition potential between seasonally sympatric phocids in the Canadian Arctic - Wesley R. Ogloff; David J. Yurkowski; Gail K. Davoren; Steven H. Ferguson (Marine Biology, 2019)

Novel observations of Atlantic walruses (Odobenus rosmarus rosmarus) in Archer Fjord, northern Ellesmere Island, Nunavut, Canada - David J. Yurkowski; Cody G. Carlyle; Uluriak Amarualik; Benjamin A. Lange; Andrew Platt; Jeff W. Higdon; D. Bruce Stewart; Adam Ferguson; Steven H. Ferguson; Christine Michel (Polar Biology, 2019)

Baffin Bay narwhal (Monodon monoceros) select bathymetry over sea ice during winter - Krista A. Kenyon; David J. Yurkowski; Jack Orr; David Barber; Steven H. Ferguson (Polar Biology, 2018)

Feeding ecology of a common benthic fish, shorthorn sculpin (Myoxocephalus scorpius) in the high arctic - Justin J. Landry; Aaron T. Fisk; David J. Yurkowski; Nigel E. Hussey; Terry Dick; Richard E. Crawford; Steven T. Kessel (Polar Biology, 2018)

Validating fin tissue as a non-lethal proxy to liver and muscle tissue for stable isotope analysis of yellow perch ( Perca flavescens ) - Meagan McCloskey; David J. Yurkowski; Christina A. D. Semeniuk (Isotopes in Environmental and Health Studies, 2018)

Spatial and temporal variation of an ice-adapted predator’s feeding ecology in a changing Arctic marine ecosystem - David J. Yurkowski; Steven H. Ferguson; Christina A. D. Semeniuk; Tanya M. Brown; Derek C. G. Muir; Aaron T. Fisk (Oecologia, 2016)

Mating ecology of beluga ( Delphinapterus leucas ) and narwhal ( Monodon monoceros) as estimated by reproductive tract metrics - Trish C. Kelley; Robert E. A. Stewart; David J. Yurkowski; Anna Ryan; Steven H. Ferguson (Marine Mammal Science, 2015)
Narwhal and beluga whales are important species to Arctic ecosystems, including subsistence hunting by Inuit, and little is understood about their mating ecology. Reproductive tract metrics vary across species in relation to mating strategy, and have been used to infer mating ecology. Reproductive tracts from beluga and narwhal were collected between 1997 and 2008 from five beluga stocks and two narwhal stocks across the Canadian Arctic. Tract length for males and females, relative testes mass for males, and tusk length for male narwhal were measured. We assessed variation relative to species, body size, stock, maturity, and season. Significant variation was found in testes mass across month and stock for beluga, and no significant difference between stock or date of harvest for narwhal. Beluga had significantly larger testes relative to body size than narwhal, suggesting they were more promiscuous than narwhal. A significant relationship was found between narwhal tusk length and testes mass, indicating the tusk may be important in female mate choice. No significant differences were found between narwhal and beluga reproductive tract length for males or females. The mating systems suggested for narwhal and belugas by our results mean the two species may respond differently to climate change.

Effects of lipid extraction and the utility of lipid normalization models on δ13C and δ15N values in Arctic marine mammal tissues - David J. Yurkowski; Nigel E. Hussey; Christina Semeniuk; Steven H. Ferguson; Aaron T. Fisk (Polar Biology, 2015)